Extraction of text from images (International Journal of Engineering and Computer Science, 2014)
Recent studies in the field of computer vision and pattern recognition show a great amount of interest in content retrieval from images and videos. This content can be in the form of objects, color, texture, shape as well as the relationships between them. The semantic information provided can be useful for content based image retrieval as well as for indexing and classification purposes. This text data is particularly interesting because text can be used easily and clearly describe the contents of an image. Since the data is embedded in an image or video in different font styles, sizes orientation, color and against a complex background the problem of extracting text becomes a challenging one. In this paper we present a method to extract text from images with complex background.